Revelation and prophethood in the Islamic worldview - Solihu, Abdul Kabir Hussain (International Islamic University Malaysia, 2009)
Belief in God’s message and messengers is a basic article of Islamic faith. Though it is sent to all humankind, revelation is not communicable directly from God to everyone at all times. The channel through which revelation became known to humankind is prophethood. Both revelation and prophethood are thus intertwined; the explanation of one will remain wanting without reference to the other. Following a textual analysis of the major Islamic references, this study explores the meaningfulness of revelation and prophethood, their function and place in the Islamic worldview, and their relevance to the contemporary era. It examines whether the prophetic message has been supplanted or subserved by humans’ intellectual enlightenment and their technological advancement.